2015
DOI: 10.1016/j.jbtep.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of acupoint stimulation in the treatment of psychological distress: A meta-analysis

Abstract: Background and objectives: Emotional Freedom Techniques (EFT) is a type of therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Reports on the outcomes of Energy Psychology methods (e.g., Feinstein, 2012) have been both criticized and defended; see, for example, critical accounts by Gaudiano, Brown, and Miller (2012) and Bakker (2013) and rebuttals of these by Sise, Leskowitz, Stein, and Tranguch (2014) and Feinstein (2014). One meta-analysis of 18 randomized controlled trials of EFT published in peer-reviewed journals found that EFT has a therapeutic effect (Gilomen & Lee, 2015), and another meta-analysis of 14 trials meeting criteria developed by the American Psychological Association's Division 12 Task Force on Empirically Validated Treatments found an overall effect size of 1.23 (Clond, 2016). EFT and related methods of Energy Psychology have been found compatible with established psychotherapeutic frameworks (Mason, 2012), including cognitive and behavioral (Benor, 2014) as well as psychoanalytic (Mollon, 2008(Mollon, , 2014.…”
mentioning
confidence: 99%
“…Reports on the outcomes of Energy Psychology methods (e.g., Feinstein, 2012) have been both criticized and defended; see, for example, critical accounts by Gaudiano, Brown, and Miller (2012) and Bakker (2013) and rebuttals of these by Sise, Leskowitz, Stein, and Tranguch (2014) and Feinstein (2014). One meta-analysis of 18 randomized controlled trials of EFT published in peer-reviewed journals found that EFT has a therapeutic effect (Gilomen & Lee, 2015), and another meta-analysis of 14 trials meeting criteria developed by the American Psychological Association's Division 12 Task Force on Empirically Validated Treatments found an overall effect size of 1.23 (Clond, 2016). EFT and related methods of Energy Psychology have been found compatible with established psychotherapeutic frameworks (Mason, 2012), including cognitive and behavioral (Benor, 2014) as well as psychoanalytic (Mollon, 2008(Mollon, , 2014.…”
mentioning
confidence: 99%
“…65 The somatic intervention used in EFT and investigated in this study (i.e., the stimulation of acupoints) has received substantial investigation. 31,61 For example, when acupoint tapping was introduced to exposure therapy protocols, the extinction of fear memories was accelerated. 66 Furthermore, biophysical markers indicating a reduction in stress after acupoint tapping have included decreased expression of genes implicated in the stress response, 67 normalization of brainwave patterns, 68,69 and hormonal changes associated with stress reduction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicated that interventions using acupoint stimulation had a moderate effect size (Hedge's g = -0.66 95% CI [-0.99, -0.33]) in reducing symptoms. 61 In EFT, the client stimulates the protocol-identified acupoints by tapping on them. Preliminary studies have suggested that tapping and other alternative ways of stimulating acupuncture points to be as effective as acupuncture needling.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated PTSD symptoms, even if subclinical, have been shown to be a risk factor for a later diagnosis of PTSD as well as depression, alcohol abuse, and health problems [62,63]. Emotion Freedom Techniques have been employed as a pre-emptive measure to treat symptoms early, enhance resiliency, and arrest the progression of the diagnosis.…”
Section: The Clinical Eft Protocolmentioning
confidence: 99%